2019
DOI: 10.26650/eor.2018.525
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of dental enamel defects and oral findings in coeliac children

Abstract: Clinical evaluation of dental enamel defects and oral findings in coeliac children PurposeTo examine dental hard and soft tissue changes of coeliac children in order to increase the awareness of the pediatric dentists in prediagnosis of especially undiagnosed coeliac disease. Materials and methodsSixty children, 28 (46.7%) boys and 32 (53.3%) girls whose ages were between 6 to 16 years were included in the present study. Thirty children who had undergone endoscopy and diagnosed with the coeliac disease in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…21 Most studies concordantly confirm that defects classified as Grade I constitute the most frequent type of DEDs. 1,6,7,15,16,[22][23][24][25][26] The overall prevalence of enamel defects among children suffering from CD varies from 17.9% to 83.5%. These inconsistencies may be caused by several factors, such as different age at CD diagnosis, strict adherence to a gluten-free diet and its duration as well as the type of population represented in the study.…”
Section: Discussionmentioning
confidence: 99%
“…21 Most studies concordantly confirm that defects classified as Grade I constitute the most frequent type of DEDs. 1,6,7,15,16,[22][23][24][25][26] The overall prevalence of enamel defects among children suffering from CD varies from 17.9% to 83.5%. These inconsistencies may be caused by several factors, such as different age at CD diagnosis, strict adherence to a gluten-free diet and its duration as well as the type of population represented in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Bramanti et al in 2014, reported that ED was more frequently observed in children with typical gastrointestinal manifestations, while aphthae were more prevalent in silent and undiagnosed CD [ 14 ]. Dental ED associated with CD are specific—they involve all the four quadrants, with color and enamel surface alteration following the sequence of dental mineralization [ 5 , 14 , 15 ]. Other ED, such as discolorations or opacities, especially if not symmetrical nor chronological, are considered unspecific [ 16 ].…”
Section: Cutaneous and Mucosal Manifestationsmentioning
confidence: 99%
“…There are multiple mechanisms responsible for oral manifestations in CD, which involve the direct effect of gluten sensitivity disorder or the consequences of malabsorption, with iron, folic acid, and vitamin (A-D-B12) deficiency [ 4 , 15 , 17 ]. Moreover, the celiac enteropathy induces an alteration of phospho–calcium metabolism, causing hypocalcemia and consequent dental demineralization [ 15 ].…”
Section: Cutaneous and Mucosal Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cause of RAS is not clear [1,3]. It is seen in otherwise healthy people, but also in various infectious and non-infectious diseases, including celiac disease (CD) [1,[6][7][8][9][10][11][12][13][14][15]. In addition, RAS is associated with genetic predisposition, iron and vitamin B12 deficiency, local mechanical injuries, stress, and hormonal imbalance [16,17,18].…”
Section: Introductionmentioning
confidence: 99%